A Bourdieuian Perspective On Social Practice And Symbolic Violence: Women's Agency In Swiped (2025) - Jeniver Nur Li Dara Dinanti; Putri Ayienda Dinanti (CV. SINAR HOWUHOWU, 2026)
Women in the technology industry are often still judged by whether powerful male figures choose to recognize their contributions, rather than by their actual skill or effort. This study looks at the film Swiped (2025) through Pierre Bourdieu's theory of social practice, focusing on the concepts of habitus, capital, and field, to understand how women's agency develops within a male-dominated tech environment. The film follows Whitney Wolfe Herd's career, starting from her early work on Tinder to her later founding of Bumble, and shows how her choices and opportunities are shaped by workplace culture, company structures, and unequal power dynamics. Using a qualitative descriptive method, this study closely examines selected scenes, dialogue, and story elements to see how these social structures influence her decisions. The findings show that her professional position is shaped not just by personal skill, but by how her internalized habits, the resources available to her, and the competitive nature of her workplace interact with one another. The film also shows that her sense of agency grows through an ongoing back-and-forth between limitation and opportunity, rather than through one single turning point. Based on this, the study argues that Swiped (2025) is more than a biopic — it works as a cultural text that reflects and shapes how we understand women's agency and power within today's digital industry.